TINGKAT PEMAHAMAN PESERTA DIDIK KELAS XI SMA SWASTA DI BEKASI TERHADAP EFIKASI DIRI DALAM BERPRESTASI - Theodora Nurmalia; Dede Rahmat Hidayat (PSIKOLOGI KONSELING, 2020)
Each school has criteria or benchmarks used to determine the final results of the learning process that has been carried out. Student learning achievement is one input or output from the school. So great is the effect of learning achievement on schools and the environment that students need to develop themselves in achieving achievement. Students are expected to have motivation in learning and improve achievement for the advancement of themselves and their environment. Self-efficacy has a role in giving a confidence or confidence to students in carrying out the task and obtain the expected results. Confidence and confidence need to be instilled in students in order to develop their abilities and be responsible for the tasks assigned to them, and obtain results according to ability. This research, reveals a description of students' understanding in carrying out learning / academic assignments so as to prepare for the future and achieve the expected goals. The number of research subjects amounted to 162 people, as students of class XI Bekasi City Private High School. The results showed 98.8% of 162 students realized that success or success could be achieved with diligent effort, 95.7% of students tried to obtain achievements to achieve their goals, 98.8% of students tried to make the assignment given by the teacher can be completed on time, 85.8% of students have the confidence to complete the task and face difficulties in completing the task (80.2%). The level of self-understanding of Class XI High School Bekasi Private School students mostly acknowledges that success or success can be achieved with diligent effort, obtaining achievements that support the achievement of ideals, as well as having confidence in completing tasks while facing difficulties